The Effect of Earnings Management, Liquidity, and Leverage on Tax Aggressiveness - Mustapa, Eka Sri Murni; Junus, Onong; Saprudin; Abdullah, Julie; Hasan, Wahyudin (Basic and Applied Accounting Research Journal, 2024)
This research aims to examine the influence of Profit Management, Liquidity, Leverage on Tax Aggressiveness. This research is a type of quantitative research using secondary data. The population in this study are mining companies listed on the Indonesia Stock Exchange for the 2018-2022 period. The sample used a purposive sampling method with a total sample of 65 consisting of 13 companies. This research uses SPSS 22. Based on the results of this research, it shows that Profit Management partially has no effect on Tax Aggressiveness because managers do not use earnings management to carry out tax aggressiveness. The Liquidity Ratio partially has a negative and significant effect on Tax Aggressiveness, because a liquidity percentage of 73% means that the company has a 73% ability to pay its short-term obligations including the tax burden. The leverage ratio partially has a negative and significant effect on Tax Aggressiveness. This research found a leverage effect of 53% where a company has high debt, so the company will tend to choose to pay its debt. Simultaneously (together) the variables Profit Management, Liquidity Ratio and Leverage Ratio have a negative and significant effect on Tax Aggressiveness.